2005
DOI: 10.1097/01.ju.0000176746.73667.3c
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity Is Frequently Undetected in Patients With Erectile Dysfunction

Abstract: Psychiatric morbidity is highly prevalent in patients with ED, potentially affecting treatment outcome. Because lifetime psychological problems were reported by more than half of the patients, a psychosocial history seems mandatory. Partner support appeared to have a significant role in the patient psychological state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 13 publications
4
40
1
Order By: Relevance
“…6,7 Even higher rates (25-55%) were reported in men attending andrology clinics. 8,9 Furthermore, Shabsigh et al 8 found that patients with ED and concomitant depression were more likely to discontinue therapy, making assessment of depression symptoms an important aspect of ED evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Even higher rates (25-55%) were reported in men attending andrology clinics. 8,9 Furthermore, Shabsigh et al 8 found that patients with ED and concomitant depression were more likely to discontinue therapy, making assessment of depression symptoms an important aspect of ED evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ED increases with age from 2% to 9% in men between the ages of 40-49 years, to 20-40% in men aged 60-69 years, and 50-100% in those aged >70 years [1,3,4]. ED is often multifactorial and includes neuronal, hormonal, vascular, myogenic and psychological causes [1,[5][6][7] with clinical implications, such as reduced quality of life [8].…”
Section: Introductionmentioning
confidence: 99%
“…15 Among males suffering from ED, are usually found to have a 2.5% to 37% prevalence of disorders of anxiety. 16 Anxiety (P= 0.0043) is significantly associated with PE in our study. Dunn KM et al, study suggests that anxiety is associated with PE.…”
Section: Discussionmentioning
confidence: 49%